Analisis Strategi Pembelajaran Active Knowledge Sharing Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti - Opet Sarianti; Martin Kustati; Rezki Amelia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is motivated because in the educational process an educator is required to improve the quality of learning in the classroom in using or creating strategies in learning to develop some of the material that must be conveyed by educators to their students, which in the Islamic Religious Education materials are not all materials that can be suitable in the use of Active Knowledge Sharing learning strategy material. The purpose of this study was to determine the analysis of active knowledge sharing learning strategies in the material of Muslim and Muslimah dresses as a mirror of personality and beauty. This research uses a literature study method or (Library research). Library research is a series of activities related to library data collection methods, reading and recording and processing research materials. The data analysis technique used is how the research data is developed and processed into a simple framework that involves a selection process and then draws a conclusion. The results of this research analysis are: The Active Knowledge Sharing learning strategy can or is suitable for use in Islamic religious education subjects in the material of Muslim and Muslimah clothing, a mirror of personality and beauty.